Pengaruh Ketidakstabilan Ketegangan Kertas terhadap Register pada Cetak Surat Kabar "X" pada Mesin Web UNIMAN 4/2 di PT Sinar Agape Press - Soelinto, Soelinto; Galingging, Rumbel; NM Sitompul, Toni (Magenta | Official Journal STMK Trisakti, 2020)
Since the increase in the price of newsprint in Indonesia, in some newspaper printers, the waste of dirty newspapers has increased, reaching more than 4%. This is due to frequent paper breaks when printing at speeds above 30,000 per hour. The paper often breaks because it is affected by the tension of the newsprint, it does not have sufficient strength when webbing is done on the web offset newspaper printing machine. And the influence of webbing also turns out to be able to affect the quality of the color print register on the web offset newspaper printing machine. To determine the existence of this influence, research was carried out on measuring the speed of the printing machine, and its relationship with paper tension. Which is measured on the paper that passes before and after the dancing roller, which is matched with observations on the results of the print register. Observations were made at low, medium, and high speeds. From the results of observations and research, it turns out that at low speeds there is a tendency for the tension of the paper to loosen, different at medium and high speeds makes the tension of the newsprint, the stretch becomes tighter. The changes in paper tension are then matched with the accuracy of the print register, it can be concluded that if the paper tension is getting better, the results of the accuracy of the print register are also getting better. ABSTRAK Semenjak terjadinya kenaikan harga kertas koran di Indonesia, di beberapa percetakan koran mengalami kenaikan waste koran kotor, mencapai di atas 4%. Hal ini dikarenakan seringnya terjadi putus kertas ketika mencetak di atas kecepatan 30.000 perjam. Kertas sering putus karena dipengaruhi oleh tegangan kertas koran tidak memiliki kekuatan yang cukup ketika dilakukan webbing di mesin Cetak Koran gulungan. Dan pengaruh webbing ini juga ternyata dapat mempengaruhi kualitas register cetak warna di mesin cetak koran gulungan. Untuk mengetahui adanya pengaruh tersebut dilakukan penelitian pada pengukuran kecepatan mesin cetak, dan hubungannya dengan ketegangan kertas. Yang diukur pada kertas yang melintas sebelum dan sesudah dancing roller, yang dicocokkan dengan pengamatan pada hasil register cetak. Pengamatan dilakukan pada kecepatan rendah, sedang, dan tinggi. Dari hasil pengamatan dan penelitian, ternyata pada kecepatan rendah ada kecenderungan ketegangan kertas mengendor, berbeda pada kecepatan sedang dan tinggi membuat ketegangan kertas koran, menjadi lebih kencang rentangannya. Perubahan-perubahan ketegangan kertas kemudian dicocokan dengan ketepatan register cetak, ternyata dapat disimpulkan bahwa jika ketegangan kertas semakin baik, maka hasil ketepatan register cetaknya juga semakin baik.